Analysis of the Utilization of Agricultural Waste Fermentation in Increasing Shallot Production - Tharmizi Hakim; Sulardi Sulardi; Muhammad M. Wasito (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Shallot farming increasing production plays a crucial role in providing fertilizer, but inorganic fertilizers are costly and rare, so that they can cause failure in shallot cultivation. The solution to the fertilizer problem can be utilizing agricultural waste in organic fertilizer. Raw materials from agricultural waste can be processed into solid and liquid organic fertilizers. The benefits of organic fertilizers increase soil fertility while also being able to change or improve soil structure and microbes. The research objective was to determine the utilization of agricultural waste in increasing shallot production. The farm waste consists of egg shells, rice husks, tofu dregs, rice washing water, goat manure, vegetable waste, banana cobs, chicken blood, pineapple skins, and empty palm fruit bunches, which are fermented into organic fertilizer. This study is new to utilizing ten types of organic waste to increase macronutrients. Research activities will be carried out in April 2022. The variables measured are plant height (cm), number of tillers (tubers), dry tuber production (g), and conversion of shallot bulb production per hectare (kg) using an analysis tool factorial randomized block design consisting of two factors, namely the first-factor solid organic fertilizer (P) with levels P0=0 kg/plot, P1=1.5 kg/plot, P2=2.5 kg/plot, and P3=3.5 kg/plot. Then the second factor is liquid organic fertilizer (C) with the treatment level C0=0 ml/liter water/plot, C1=250 ml/liter water/plot, C2=500 ml/liter water/plot, C3=750 ml/liter water/ plot. The research variables were plant height (cm), number of tillers (tubers), dry tuber production (g), and shallot production conversion per hectare (kg). The results showed a significant effect on solid fertilizers at the P3 level compared to the P2, P1, and P0 levels. In contrast, the liquid fertilizer treatment at the C3 level significantly affected the C2, C1, and C0 levels.